An ADRL Approach of Long Terms and Short Term Effects of Foreign Labour Employment on Nepal’s Econo - Kharel, Khom Raj; Upadhyaya, Yadav Mani; Khadka, Ramesh Bahadur (Janapriya Journal of Interdisciplinary Studies, 2024)
Foreign labor employment plays a critical role in shaping Nepal’s economy, influencing GDP growth and remittance inflows, with both long-term and short-term effects that warrant detailed econometric analysis to guide policy and economic planning. The study aims to comprehensively evaluate the status of foreign labor employment in Nepal and its impact on the economy, integrating insights from various methodologies, including status assessment and economic evaluation. Econometric analysis, particularly the ARDL model, confirms a long-term relationship between GDP, foreign employment, and remittances, with implications for policy and planning. The findings are that the expected growth in foreign labor migration to Nepal implies potential wide-ranging implications for the country’s economy, social structures, and policy landscape, affecting factors such as employment dynamics, remittance inflows, social cohesion, and infrastructure demand. The outcomes of the error correction representation for the chosen ARDL model further reinforce the presence of a robust long term relationship among the variables, with the coefficient of the error term (-1.069490) at the first difference exhibiting a statistically significant negative sign. This underscores the swift dynamics within the analyzed relationships, with the speed of adjustment from the previous year’s disequilibrium in GDP to the current year’s equilibrium determined to be 106.94%. In conclusion, Nepal’s anticipated increase in foreign labor migration has significant implications for its economy, social structures, and policy landscape, affecting employment dynamics, remittance inflows, and infrastructure demand.